PENGARUH PERMAINAN CARRYING BALL ON POLES TERHADAP PERKEMBANGAN SOSIAL ANAK DI TAMAN KANAK-KANAK DELIMA BANDARA - Damayanti, Melly; Serli Marlina (Bunayya, 2026)
This research is motivated by the suboptimal social development of children in the current technological era, where excessive device usage has hindered the growth of their cooperation, communication, and independent conflict-resolution skills. The primary objective of this study is to examine the effect of the collaborative game "Carrying Ball on Poles" on the social development of early childhood. The research employed a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design). The subjects consisted of a single group assigned to the experimental class. Data were collected through structured observations using a validated social development assessment instrument. The data analysis used an independent-samples t-test to compare pre-test and post-test results. The findings indicate a significant improvement in children's social skills through intensive interaction that requires physical synchronization and effective communication during the game. This study concludes that innovative group-play-based learning strategies are essential to optimizing children's social potential holistically.